THE ECOLOGY AND DISTRIBUTION OF FREYCINETIA GAUD. (PANDANACEAE; FREYCINETOIDEAE) IN THE INDONESIAN NEW GUINEA - SINAGA, NURHAIDAH IRIANY; MEGIA, RITA; HARTANA, ALEX; KEIM, ARY PRIHARDHYANTO (REINWARDTIA, 2010)
SINAGA, N. I., MEGIA, R., HARTANA, A., KEIM, A. P. Ecology and distribution of Freycinetia Gaud. (Pandanaceae; Freycinetoidea) in Indonesian New Guinea. Reinwardtia 13(2): 189-197. - The study mainly concerns with the species of Freycinetia that occurs in the Indonesian New Guinea, including the provinces of Papua and Papua Barat. The study indicates that almost all species of Freycinetia in the Indonesian New Guinea prefer high humidity and abundantly occur along rivers, except for the members of the group of species with imbricate leaves, which inhabit also secondary forests. Futhermore, the members of this group have never been found within the range of 1700 to 3000 m altitudes. This highest range of altitudes is specifically occupied by the members of the groups of species with semi imbricate and grass-like leaves. The costal forests are inhabited by the groups of species with semi and non imbricate leaves. Indonesian New Guinea shares many species with Papua New Guinea, except for the members of the group of species with semi imbricate leaves, which are more common in Indonesian New Guinea than in Papua New Guinea. On the contrary, the members of the group of species with grass-like leaves are more common in Papua New Guinea and becoming rare toward the Indonesian site and becoming absent in the Vogelklop (Birds head), except for F. polyclada which is commonly found in Sorong. Indonesian New Guinea possesses 34 species exclusively distributed in the area, while Papua New Guinea has 72 species. The two areas share 52 species. Only five species have extra New Guinean distributions, i.e. F. excelsa, F. funicularis, F. marginata, F. percostata, and F. scandens.